SIMULATED HYPOGRAVITY: EFFECT ON GLUTAMIC ACID METABOLISM IN TAGETES PATULA - OPUTA, C. OTUNWA (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
L. Proline-UL-14C was fed to shoot of intact 51 day old Tagetes patula plants grown normally or on a horizontal clinostat rotating at 15 rev/hr. After 24 hr. incubation. 14C incorporated into different amino acids of different tissues (stem plus leaves. and flowers) was determined by autoradiography. Also, glutamic acid decarboxylase activity in the leaves of control and clinostated plants was determined. It was observed that glutamic acid decarboxylase activity in the control plant was about 2-fold that in gravity compensated plants (grown on horizontal clinostats). In the flora shoot of control plants. about 62% of the total radioactivity, which was incorporated into the amino acid fraction, was lodged in aminobutyric acid (GABA). In contrast, GABA was not labelled in the gravity compensated plants. Rather, practically all the radioactivity (100%) was incorporated into what was suspected to be a peptide. The interpretation of these results is that under normal conditions the enzyme glutamic acid decarboxylase is active and so glutamic acid is converted to aminobutyric acid by decarboxylation reaction. Under hypogravity, this enzyme is perhaps inactive and another enzyme probably a glutamyl transferase system becomes operative and utilises the glutamate for peptide formation, A scheme showing the biogenic relationship between proline, glutamic acid. aminobutyric acid and peptides is discussed.